Emerging Role of Myeloid-derived Suppressor Cells in the Biology of Transplantation Tolerance. Issue 3 (March 2020) - Shao, Liang; Pan, Shan; Zhang, Qiu-ping; Jamal, Muhammad; Rushworth, Gerard-Martin; Xiong, Jie; Xiao, Rui-jing; Sun, Jia-xing; Yin, Qian; Wu, Ying-jie; Lie, Albert K.W.
Abstract : Myeloid-derived suppressor cells (MDSCs), a heterogeneous population of myeloid cells, are characterized by their immunosuppressive abilities through the secretion of various cytokines such as inducible nitric oxide synthase, nitric oxide, reactive oxygen species, transforming growth factor-β, and arginase-1. Accumulating evidence highlights its potential role in maintaining immune tolerance in solid organ and hematopoietic stem cell transplantation. Mechanistically, MDSCs-induced transplant tolerance is mainly dependent on direct suppression of allogeneic reaction or strengthened cross-talk between MDSCs and Treg or NKT cells. Adopted transfer of in vitro– or in vivo–induced MDSCs by special drugs therefore becomes a potential strategy for maintaining transplantation tolerance. In this review, we will summarize the previously published data about the role of MDSCs in the biology of transplantation tolerance and gain insights into the possible molecular mechanism governing this process.